Analysis of The Limits of Criminal Acts of Gambling in The System of Acquiring Virtual Assets Through Loot Crates in Virtual Games - Pradana, Indra Kurnia Okta; Aprilianda, Nurini; Sulistio, Faizin (International Journal of Business, Law, and Education, 2023)
The development of globalization and technological advances influences the progress of the creative industry, particularly in the virtual gaming sector, commonly known as online games. As time progresses, the online gaming industry is rapidly evolving, both in terms of its audience and the entrepreneurs involved. This sector enables easy selling of various items related to online games. With the increasing number of enthusiasts due to the changing times, gaming companies are introducing innovations to captivate players' interest.One such innovation is the introduction of a new category of virtual assets in online games, commonly referred to as Loot Crates. These are virtual assets in online games that can be purchased using real currency or other payment methods, such as in-game currency. The Loot Crate system involves a mechanism that provides virtual assets randomly, incorporating an element of luck to obtain desired assets. However, the random nature of Loot Crates raises concerns about meeting the elements of gambling offenses.The Loot Crate system, implemented by various producers, operates as an electronic transaction and is subject to the Electronic Information and Transactions Law No. 11 of 2008, in conjunction with Law No. 19 of 2016. According to these laws, one of the prohibited actions, as stated in Article 27, Paragraph 2, is "Any person intentionally and without right distributes and/or transmits and/or makes electronically stored information and/or electronic documents that contain gambling content."Please note that the translation may not capture the full legal nuances, and legal advice may be necessary for a precise interpretation.